2017
DOI: 10.11648/j.ajaf.20170503.12
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 60 Years of Intensive Rice Cropping on Clay Minerals in Soils Due to Si Exportation

Abstract: Abstract:Rice is cultivated as staple for over half of the World's population. In Camargue (South of France) rice fields have been established on very young soils developed from historic fluvial deposits of the Rhône River. The comparison of clay mineralogy in a paddy field cultivated for 60 years and in a control shows a significant increase of the clay crystallinity in the paddy field soil, which implies a decrease of their solubility. In the paddy soils, phytoliths, poorly crystallized clays, such as smecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…More recently, it was shown at Morrow plot experiment field (USA) that continuous cropping for 110 years led to an increase in fine clay particles (<0.05 mm) [18], which is an indicator of clay mineral dissolution. In a rice paddy field in Camargue (France), the decreased crystallinity of smectite was attributed to rice cultivation and its subsequent Si uptake [19]. However, no associated Si concentrations in plants were reported in that study, or in the other abovementioned studies.…”
Section: Introductionmentioning
confidence: 70%
“…More recently, it was shown at Morrow plot experiment field (USA) that continuous cropping for 110 years led to an increase in fine clay particles (<0.05 mm) [18], which is an indicator of clay mineral dissolution. In a rice paddy field in Camargue (France), the decreased crystallinity of smectite was attributed to rice cultivation and its subsequent Si uptake [19]. However, no associated Si concentrations in plants were reported in that study, or in the other abovementioned studies.…”
Section: Introductionmentioning
confidence: 70%
“…The correlation of Si CaCl2 with pH indicated that Si CaCl2 concentration may be controlled by Si adsorbed on the surface of soil minerals and/or by the soil weathering state 25,26 . The correlation of Si CaCl2 with the < 2 µm fraction can be attributed to the presence of small phytoliths 49 , clay mineral dissolution 50 , or adsorption onto clay minerals 51 . Nevertheless, while Si CaCl2 linearly increased with the < 2 µm fraction in non-cultivated soils regardless of parent material (Fig.…”
Section: Soil Parent Material/typementioning
confidence: 99%
“…According to Vandevenne et al (2012) agriculture may have disturbed the natural cycle of Si because plant materials do not return to the field and are injected into the urban cycle. Several perturbations have been documented in the surface soil horizons: depletion of the phytolith pool (Struyf et al, 2010;Clymans et al, 2011;Guntzer et al, 2012;Vandevenne et al, 2015a) and a decrease of crystallinity of clays (Irfan et al, 2017). Besides, repeated crop removal can reduce the concentration of potentially available Si to the extent that Si fertilization is necessary (Datnoff and Rodrigues, 2005;Meunier et al, 2008;Savant et al, 1997).…”
Section: Introductionmentioning
confidence: 99%